Modulation of Human 5-Hydroxytryptamine Type 3AB Receptors by Volatile Anesthetics and n-Alcohols - Stevens, Renna (J Pharmacol Exp Ther, 2005)
Functional 5-hydroxytryptamine type 3 (5-HT(3)) receptors can be formed by 5-HT(3A) subunits alone or in combination with the 5-HT(3B) subunit, but only the 5-HT(3A) receptor has been previously studied with respect to the modulation by volatile anesthetics and n-alcohols. Using two-electrode voltage-clamp, we show for the first time the modulation of heteromeric human (h)5-HT(3AB) receptors, expressed in Xenopus oocytes, by a series of n-alcohols and halogenated volatile anesthetics. At twice their anesthetic concentration, compounds having a molecular volume of less than 110 Å(3) enhanced submaximal 5-HT-evoked current. Compounds larger than 110 Å(3) inhibited submaximal 5-HT-evoked current. In experiments examining 5-HT concentration-response relationships, chloroform and butanol caused a slight decrease in the 5-HT EC(50). Sevoflurane and octanol inhibited 5-HT-evoked current at all 5-HT concentrations tested but had no effect upon the 5-HT EC(50). Compared with previous data on homomeric h5-HT(3A) receptors, the presence of the h5-HT(3B) subunit reduces the enhancement of h5-HT(3) receptors by smaller halogenated volatile anesthetics and n-alcohols. In summary, these results suggest that heteromeric h5-HT(3AB) receptors are modulated by halogenated volatile anesthetics at clinically relevant concentrations, in addition to n-alcohols, suggesting that these receptors may be another physiological target for these compounds. The modulation is dependent upon the molecular volume of the compound, further supporting the concept of an anesthetic binding pocket of limited volume common on other Cys-loop ligand-gated ion channels. Incorporation of the 5-HT(3B) subunit alters either the anesthetic binding site or the allosteric interactions between anesthetic binding and channel opening.